The effect of straight-line and accelerated depreciation rules on risky investment decisions: An experimental study - Hagen Ackermann; Martin Fochmann (Arbeitskreis Quantitative Steuerlehre (arqus), 2014)
The aim of this study is to analyze how depreciation rules influence the decision behavior of investors. For this purpose, we conduct a laboratory experiment in which participants decide on the composition of an asset portfolio in different choice situations. Using an experimental environment with different payment periods, we show that accelerated compared to straight-line depreciation can increase the willingness to invest as hypothesized by theory. Additionally, we are able to replicate the unexpected finding of Ackermann et al. (2013) - that introducing a subsidy leads to a lower willingness to take risk although the net returns are kept constant - with our setting which is different to their experimental environment.
Keywords: C91; D14; H24; 330; Taxation; Straight-line Depreciation; Accelerated Depreciation; Tax Perception; Risk Taking Behavior; Portfolio Choice; Behavioral Taxation